Development of two-fingered underactuated robot gripper using 3D printer - Sadun, Amirul Syafiq; Jalani, Jamaludin; Nasir, Siti Hana; Roslan, Mohd Nazrul; Hashim, Hairulazwan; Mohd Anuar, Syazwani (IOP Publishing, 2019)
This research present the development of a two-fingered underactuated robot gripper by using 3D printed machine with a material of Polylactic acid or PLA. The gripper design consist of two individual servo motors that drives the finger movement to perform a certain amount of grasping force. The new design of the finger using Solidworks was inspired by several existing robot gripper however with a low cost approach to obtain a good finger tracking and angular control. The fully fabricated and assembled gripper was then tested to determine the operation results during basic grasping and ungrasping by connected to Arduino Mega and MATLAB software. The angular data during the operation shows that the gripper successfully perform a stable operations despite some minor disturbance due to the mechanical defect on the servo plate. Further analysis will be conducted in the future in order to identify the full capability of the gripper in real world application such as force control operations